Does foreign investment improve technical efficiency of manufacturing? Evidence from the Republic of Serbia - Nikolic, Ivan (Industrija, 2021)
Based on a balanced panel data on a sample of 92 manufacturing groups over the period 2010-2019 this paper finds strong evidence for the existence of positive impact of foreign direct investment on technical efficiency. Throughout this period Serbia lost 28% of the potential output of the manufacturing sector due to technical inefficiency. The finding is directly supported by the results at the level of the observed groups. Thus, the greatest increase in technical efficiency is in branches with a high share of foreign ownership, such as: production of motor vehicles, production of chemicals, and production of wire and cable equipment. The methodology is based on stochastic frontier analysis - within that, 'true' random effects model. The paper contributes to the understanding of potential effects on foreign invested enterprises on domestic economy in general and local enterprises performance in particular. Thus it importantly assists policy making by the government of developing countries, where FDI is believed to create technical spillovers on domestic enterprises.
Keywords: Technical Efficiency, Foreign direct investment (FDI), Stochastic frontier model, Serbian manufacturing